How did Immigrants fare in the Irish Labour Market over the Great Recession? - Kelly, Elish (OECD Economics Department Working Papers, 2016)
This paper identifies the labour market impact of the Great Recession on immigrants compared to natives and how this relationship has evolved since the downturn. We find that the employment penalty suffered by immigrant workers, relative to native workers, increased significantly over the Irish recession and persisted during the subsequent recovery. Differences in labour market outcomes between immigrants and natives were accentuated by the recession, when the employment penalty was the highest. Secondly we conclude that the more recent evolution of the employment penalty appears to be related to a composition effect, as many refugee immigrants with weak labour market attachment became naturalised citizens during the recession. This suggests that the difficulties that some immigrants experience in the labour market would be under-estimated without taking due account of naturalisation processes, as is done in this paper for the first time in Ireland. This working paper relates to the 2015 OECD Economic Survey of Ireland (http://www.oecd.org/eco/surveys/economic-survey-ireland.htm)